Primary Hodgkin’s Lymphoma With Chest Wall Ulceration and Hypereosinophilia: A Rare Presentation and Diagnostic Dilemma - Syahril, Wan Ahmad; Rafeah, Tumian Nur (Indian Journal of Case Reports, 2018)
Hodgkin